2016
DOI: 10.1179/2151090314y.0000000024
|View full text |Cite
|
Sign up to set email alerts
|

Computerized occlusal analysis as an alternative occlusal indicator

Abstract: The reported advantages to accurately indicate occlusal contacts make the computerized occlusal analysis system a better occlusal indicator when compared with other non-digital convention indicator materials available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 30 publications
1
76
0
7
Order By: Relevance
“…A significantly higher occlusal force percentage was found in the posterior region than the anterior region, which is in agreement with previous studies 21–23 . In addition, a slight difference in the bilateral force distribution was found, indicating slight asymmetry, even in patients with normal occlusion.…”
Section: Discussionsupporting
confidence: 93%
“…A significantly higher occlusal force percentage was found in the posterior region than the anterior region, which is in agreement with previous studies 21–23 . In addition, a slight difference in the bilateral force distribution was found, indicating slight asymmetry, even in patients with normal occlusion.…”
Section: Discussionsupporting
confidence: 93%
“…[18][19][20] First introduced in 1987, T-Scan (Tekscan, Inc., South Boston, MA, USA) is a computer-assisted dental occlusion analyzer, i.e., able to record quantifiable relative occlusal force and contact time sequencing in real time. 18,21,22 A vast body of evidence supports the acceptable accuracy of computerized occlusal analysis as an occlusal indicator. 18,[21][22][23][24] The aim of this study was to evaluate postinsertion posterior single-implant restoration occlusion changes at different intervals using the T-Scan III computerized occlusal analysis system.…”
Section: 5005/jp-journals-10024-2151mentioning
confidence: 99%
“…18,21,22 A vast body of evidence supports the acceptable accuracy of computerized occlusal analysis as an occlusal indicator. 18,[21][22][23][24] The aim of this study was to evaluate postinsertion posterior single-implant restoration occlusion changes at different intervals using the T-Scan III computerized occlusal analysis system. The null hypothesis was that the occlusion developed at placement of single implantsupported prostheses opposed by natural teeth would not change over time.…”
Section: 5005/jp-journals-10024-2151mentioning
confidence: 99%
“…Kevin et al [17] reported that computerized occlusal analysis system provide quantifiable force and time variance in a real-time window from the initial tooth contact into maximum intercuspation and therefore provides valuable information.…”
Section: Discussionmentioning
confidence: 99%